Preparation and Characterization of Cellulose Acetate from Pandanus tectorius via Microwave Irradiation - Rizkiana, Meta Fitri; Amrullah, Abdul Malik Karim; Elisah, Nor; Amini, Helda Wika; Palupi, Bekti; Rahmawati, Istiqomah; Fachri, Boy Arief (Indonesian Journal of Chemical Research, 2024)
This research focuses on extracting cellulose from thorn pandan and evaluating its potential as a raw material for cellulose acetate. Thorn pandan contains polysaccharides, especially cellulose. In its fabrication process, cellulose acetate is produced from cellulose acetylation reaction. Cellulose is extracted using the Microwave-assisted Extraction method with variations in NaOH concentration (1, 2, and 3%), H2O2 concentration (10, 20, and 30%), and time variables (20, 40, and 60 minutes). Extraction optimization was performed with Response Surface Methodology (RSM) model BBD (Box-Behken Design). Several characterizations were carried out to determine the characteristics of cellulose acetate, namely Degree of Acetylation, FT-IR spectroscopy and X-Ray Diffraction (XRD). The highest cellulose yield obtained in the extraction process was 50.7% with a variable of 3% NaOH, 30% H2O2 and 60 minutes. XRD analysis shows the angle value 2θ = 22.53798° of thorn pandan cellulose structure is almost similar to commercial cellulose. FTIR functional group identification of cellulose acetate showed the presence of carbonyl (C=O) and (C-O Acetyl) group, respectively seen at wave numbers 1734 cm-1 and 1256 cm-1. The acetyl content of cellulose acetate from thorn pandan produced is 35.475%. Therefore, thorn pandan biomass has the potential as a raw material for making cellulose acetate.